2011
DOI: 10.1007/s00248-011-9963-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in the Cecum of the World’s Largest Living Rodent (Hydrochoerus hydrochaeris)

Abstract: The capybara (Hydrochoerus hydrochaeris) is the world's largest living rodent. Native to South America, this hindgut fermenter is herbivorous and coprophagous and uses its enlarged cecum to digest dietary plant material. The microbiota of specialized hindgut fermenters has remained largely unexplored. The aim of this work was to describe the composition of the bacterial community in the fermenting cecum of wild capybaras. The analysis of bacterial communities in the capybara cecum is a first step towards the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
9
2
Order By: Relevance
“…Early research into lignocellulose digestion in the beaver GI tract identified cellulase activity in ceacal contents [ 19 ], although the microbial basis of this activity was not investigated. Our results demonstrate that the microbial community found in the ceacum and feaces of the beaver is similar to that found in other hindgut fermenters [ 6 , 16 , 17 , 31 ]. These bacterial communities in the beaver are both dominated by Firmicutes and Bacteroidetes; a characteristic that is common within all mammalian guts [ 6 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Early research into lignocellulose digestion in the beaver GI tract identified cellulase activity in ceacal contents [ 19 ], although the microbial basis of this activity was not investigated. Our results demonstrate that the microbial community found in the ceacum and feaces of the beaver is similar to that found in other hindgut fermenters [ 6 , 16 , 17 , 31 ]. These bacterial communities in the beaver are both dominated by Firmicutes and Bacteroidetes; a characteristic that is common within all mammalian guts [ 6 ].…”
Section: Discussionsupporting
confidence: 82%
“…Rodents are primarily herbivores and utilize hind-gut fermentation to break down cellulosic feeds [ 13 ]. With the exception of the mouse ( Mus musculus ) and the lab rat ( Rattus norvegicus ), which serve as model systems for understanding the interactions between host and gut microbiome [ 14 , 15 ], few studies have examined the microbial communities in the ceacum of rodents [ 16 , 17 ]. Of particular interest, the microbial basis of lignocellulose digestion in one of the most iconic Canadian rodents, the beaver (genus Castor ), has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal sampling serves as an alternate for more laborious and invasive sampling from, in these circumstances, commercial, domesticated livestock from an active farm. The phyla Firmicutes and Bacteroidetes were identified as the predominant phyla in the microbiota of all the domesticated herbivores in this study; however, this trend has not been universal for other studies and animals (Barker, Gillett, Polkinghorne, & Timms, 2013;García-Amado et al, 2012;Ishaq & Wright, 2012;Li et al, 2013). Ley et al identified Firmicutes and Bacteroidetes as the phyla found most ubiquitous in the vertebrate microbiota .…”
Section: Discussioncontrasting
confidence: 52%
“…The phyla Firmicutes and Bacteroidetes were identified as the predominant phyla in the microbiota of all the domesticated herbivores in this study; however, this trend has not been universal for other studies and animals (Barker, Gillett, Polkinghorne, & Timms, ; García‐Amado et al., ; Ishaq & Wright, ; Li et al., ). Ley et al.…”
Section: Discussioncontrasting
confidence: 49%
“…Clostridiaceae, the third most abundant family, was not reported as a main bacterial family in rabbits by Massip et al (2012); however, it was present in rabbit caeca (Bäuerl et al, 2014), and was a dominant family in the capybara (García-Amado et al, 2012) and healthy horses (Steelman et al, 2012). Members of the Clostridiaceae family have been found to prefer simpler carbohydrates, rather than the fibrous components utilised by the Lachnospiraceae and Ruminococcaceaea, and its prevalence in the caecum was thus somewhat surprising (Biddle et al, 2013).…”
Section: The Microbiota Profilementioning
confidence: 97%